The effectiveness of kinesio tape application on flexibility among sedentary people / Nazatul Liyana Ideris Shah - Ideris Shah, Nazatul Liyana (Faculty of Sport Science and Recreation, 2016)
The purpose of this study is to determine the effectiveness of the kinesio tape application on flexibility among sedentary people. A total of thirty healthy sedentary subjects (N=30) were selected via stratified random sampling. The subjects randomly in any age. The study involved 15 female and 15 male subject, aged between 20 years old to 36 years old. Results show that there was a significant difference (p<0.05) for flexibility parameters, sit and reach test (SR) (p<0.01) and the trunk range of motion for the both sides were (DROM) (p<O.OI) when the subjects used Kinesio tape. In the trunk range of motion for both sides right and left side (TROM) (P<O.OI). There was is significance difference in the flexibility of the sedentary subjects, when kinesio tape was applied. In conclusion, the findings in this study have shown that the effectiveness of the kinesio tape on the flexibility among the sedentary people.